Proposed Framework for Tax Accounting on the Uses of Artificial Intelligence (Entrepreneurship Journal for Finance and Business, 2025)
The research aims to identify the tools and areas of artificial intelligence that are subject to tax in the digital environment, and how to account for them in light of the problems and challenges resulting from the absence of legislation that is compatible with the digital nature of such transactions. This is done by developing a proposed integrated framework for tax accounting in the context of digital transformation and artificial intelligence. The research reached several conclusions, the most important of which is the lack of legislation covering tax transactions in the digital environment and in light of the variables of artificial intelligence. This is in addition to some instructions that have not been unified at the international level, in addition to the lack of mandatory implementation. The research included several recommendations, most notably the need to unify legislation related to tax accounting at the global level and the need to keep pace with global developments.